(untitled) (Revista de Crítica Literaria Latinoamericana, 2011)
This article delves into one of the key aspects of Macedonio Fernández’s writing: denial as a way of idealism and the literary productivity that such an attitude creates. Our essay consists of three parts: Macedonio ’s own denial of identity, his negation of writing itself and, finally the overarching denial of the act of reading (and of the reader’s existence), unlike other critical studies which focused on the last figure in this Argentine author. In this way, we will attempt to explain his peculiar and ambitious plan, which takes the shape of a very thick nothingness.